Acromion-axillary nerve distance and its relation to the arm length in the prediction of the axillary nerve position: a clinical study - Cem Yildirim; Mehmet Demirel; Erhan Bayram; Mehmet Ekinci; Murat Yılmaz (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Because of the broad anatomic variation in the course of the axillary nerve, several cadaveric studies have investigated the acromion-axillary nerve distance and its association with the humeral length to predict the axillary nerve location. This study aimed to analyze the acromion-axillary nerve distance (AAND) and its relation to the arm length (AL) in patients who underwent internal plate fixation for proximal humerus fractures. Methods The present prospective study involved 37 patients (15 female, 22 male; the mean age = 51 years, age range 19–76) with displaced proximal humerus fractures treated by open reduction and internal fixation. After anatomic reduction and fixation were achieved, the following parameters were measured in each patient before wound closure without making an extra incision or dissection: (1) the distance from the anterolateral edge of the acromion to the course of the axillary nerve was recorded as the acromion-axillary nerve distance and (2) the distance from the anterolateral edge of the acromion to the lateral epicondyle of the humerus was recorded as arm length. The ratio of AAND to AL was then calculated and recorded as the axillary nerve index (ANI). Results The mean AAND was 6 ± 0.36 cm (range 5.5–6.6), and the mean arm length was 32.91 ± 2.9 cm (range 24–38). The mean axillary nerve ratio was 0.18 ± 0.02 (range 0.16 to 0.23). There was a significant moderate positive correlation between AL and AAND (p = 0.006; r = 0.447). The axillary nerve location was predictable in only 18% of the patients. Conclusion During the anterolateral deltoid-splitting approach to the shoulder joint, 5.5 cm from the anterolateral edge of the acromion could be considered a safe zone to prevent possible axillary nerve injury.